Reactions to COVID-19, information and technology use, and social connectedness among older adults with pre-frailty and frailty - Chen, Annie T.; Ge, Shaoqing; Cho, Susie; Teng, Andrew K.; Chu, Frances; Demiris, George; Zaslavsky, Oleg (Geriatric nursing (New York), 2021)
•Coronovirus Disease 2019 (COVID-19) has serious implications for older adults.•Qualitative analysis of an online discussion by older adults with frailty.•We analyzed 60 posts using a general inductive analytic method.•Themes included impacts on daily life, perceptions, information, and technology use.•Our study provides insight into ways to support older adults in pandemics. The emergence of Coronavirus Disease 2019 (COVID-19) and social distancing measures has serious implications, particularly those age 65 and older. We performed a qualitative analysis of online discussion data generated by older adults with pre-frailty and frailty while subject to a state stay-at-home order. We provided participants with prompts relating to the public health emergency, collected 60 posts, and analyzed them using a general inductive analytic method. We report on: (1) the impact of the pandemic on daily life; (2) preparedness, perceptions, and behavior; (3) information and technology use; and (4) social impacts. Participants’ lives of changed in many ways, including the adoption of precautionary measures and altered daily routines. Participants experienced negative emotional consequences including stress, worry, and anxiety. Information and technology use kept participants informed and connected. Participants reported varying degrees of preparedness. Our study findings provide insight into ways to support vulnerable older adults in pandemic circumstances.